Modification of the Engineering Properties of Road Base Course Soil Materials with Cement and Polyethylene Terephthalate (PET) - Sati C. NSHOL; Saeed Y. UMAR; Suleiman A. YERO (FUDMA Journal of Engineering and Technology, 2025)
Highways have high capital costs, which include the cement or lime used in soil hardening. However, alternative construction materials such as recycled plastic can be used to reduce the cost and mitigate the effect of environmental pollution by plastic disposal. This study aimed at improving the engineering properties of road base course soil materials with Cement of 2% and Polyethylene terephthalate (PET) of size 10mm x 5mm with (0.2-0.5) % inclusion. The soil was obtained from Dungulbi borrow pit at latitude 10.27485990N, longitude 9.95061660E, and Altitude 550m in Bauchi L.G.A of Bauchi State. The design expert software used for the experiment gave rise to 13 mix proportions. The chemical analysis of the soil revealed that, the soil is laterite due the silica sesquioxide (S-S) ratio of 1.25. The soil is classified as A-7-6 group in accordance with the American Association of State Highways and Transportation Officials (AASHTO). Soil classification system classified it as CL with group index (GI) of 17. The unconfined compressive strength (UCS) value of 673kN/m2 for stabilized soil with cement and PET indicated an improvement compared with natural soil value of 394kN/m2 the California bearing ratio (CBR) for unsoaked and soaked with the value of 79% and 29% respectively, compared to the natural soil of 25% and 13% respectively, which indicates an adequate improvement in the bearing capacity of stabilized soil. Optimization value of factors responses and desirability are PET, 10.5%, Cement 2%, CBR unsoaked 74%, and soaked 26%. The UCS, at 28days is 671kN/m2 with desirability value of 0.8. The analysis of variance (ANOVA) revealed that F-value was 147.88 with P-value less than 0.0001 which indicated that the un soaked CBR quadratic model of stabilized soil is significant. The same applicable to soaked and UCS of 28 days. This research work can aid in solving two current problems of the modern world: pollution reduction of PETS and using them to improve the engineering properties of weak soils.